REACTIVE CHANGES IN THE PANCREAS IN HYPOTHYROIDISM - Niyazov Norbek Kurbanovich; Akhmedova Sayyora Muxamadovna; Mirsharopov O‘tkir Mirsharopovich; Djabbarov Nurbek Narjigitovich (Journals Park Publishing, 2024)
For the study, we used the offspring of rats born from control and experimental white laboratory rats - mothers under conditions of hypothyroidism. The results of the study showed that the introduction of Mercazolil into the pancreatic lobules of experimental rats led to changes associated with the normalization of the structural organization of the pancreatic cranium, interlobular connective tissue with the formation of fibrous tissue components, as well as the disappearance of choroid edema observed in the interlobular connective tissue.
Keywords: mercazolil, pancreas, pancreatic lobes.